Analisis Tatabahasa Visual Dalam Iklan Jenama Fesyen Pada Siaran Pempengaruh Brunei Di Media Sosial Instagram (International Journal of Linguistics and Indigenous Culture, 2024)
Media has become a part of society that utilizes signs and markers on featured images. Social media users have incorporated semiotic resources such as writing, speech, use of images or videos, layout and color while communicating. This shows that communication nowadays is no longer limited to the use of words only or a conventional approach. In addition, social media can also be used to promote sales products by collaborating between brands and famous figures or social media influencers because the role of social media influencers shows a very convincing potential in helping the development of the branding of a product or service. Therefore, this study was conducted with the aim of providing a comprehensive overview of the visual elements in fashion brand advertisements uploaded by Bruneian influencers on Instagram. The method of the study was a descriptive qualitative and the data collection method in this study consists of literature review and documentation. The data sources are collected from 4 Bruneian influencers who posted some fashion advertisements, especially women's hijabs and dresses from several different brands. All data collected was analyzed using the Visual Grammar Design framework model from Kress and van Leeuwen (2006). The results of the study show that the advertisements uploaded by the Brunei influencers meet the criteria stated by Kress and van Leeuwen. The researcher found that the posts uploaded by Bruneian influencers are often represented using conceptual structures. In addition, the researcher found that in the interaction component, Bruneian influencers make more eye contact (demand) than offer. The social distance for the uploaded photo on every posts is also taken with a medium shot, long shot or very long shot. This social distance can ensure that the message from the advertised product can be well communicated to the audience. In fact, each post also has a similarity in terms of point of view, which is subjectivity because each picture shows the participant's involvement with the advertised product and each picture is taken from a frontal angle. Lastly, the researcher found that in terms of compositional components, the products advertised by Bruneian influencers appear to be on the left side (given) and also on the right side (new). However, more are seen to be in the middle (ideal) because this ad product consists of clothes or hijabs used by the participants.